Revolusi Tiktok: Mendefinisikan Ulang Pemasaran Media Sosial - Roy Irawan; Isroni Isroni; Sukmono Bayu Adhi; Dedi Suharyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the dynamics of social media marketing effectiveness within PT Migas Utama Jabar, focusing on the utilization of TikTok platform and changes in social media consumption habits. Through quantitative analysis utilizing Smart PLS, data from a sample of 100 individuals within the organization were examined. The results reveal significant direct effects of TikTok utilization and audience engagement on social media marketing effectiveness, highlighting the importance of leveraging innovative platforms to foster active engagement with the target audience. However, changes in social media consumption habits were not found to have a significant indirect effect on social media marketing effectiveness mediated through audience engagement. These findings underscore the significance of adapting strategies to capitalize on emerging trends and platforms to enhance brand visibility and engagement. The study provides valuable insights for PT Migas Utama Jabar and other organizations aiming to navigate the evolving landscape of social media marketing, emphasizing the importance of audience-centric approaches in achieving marketing objectives and sustaining competitiveness in the digital era. Keywords: Social Media Marketing, Tiktok, Audience Engagement, Social Media Consumption Habits, Marketing Effectiveness